Preparation method for deriving defect-rich transition metal oxide catalyst by utilizing bio-based complexing precursor
By preparing defect-rich transition metal oxide catalysts using bio-based complexed precursors and mechanochemical methods, the problems of long reaction time, agglomeration, and uneven composition of transition metal oxide catalysts were solved, achieving high catalytic efficiency and large specific surface area.
Patent Information
- Application Number
- CN202510723014.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-10-28
AI Technical Summary
Existing methods for preparing transition metal oxide catalysts result in excessively long reaction times, are prone to agglomeration or have insufficiently uniform composition, and require further optimization of specific surface area.
Defect-rich transition metal oxide catalysts were prepared using bio-based complexing precursors and mechanochemical methods. By utilizing the highly branched bundle structure and hydroxyl-rich properties of the bio-based complexing agent, surface oxygen vacancies were constructed through mechanical ball milling to prepare layered catalysts.
It improves the stability and functionality of the catalyst, increases the exposure opportunities of active sites, has a good catalytic effect, and the conversion rate can reach more than 90%. The specific surface area can reach 81.8 m2/g, avoiding the defects of traditional methods.
Smart Images

Figure CN120838403A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a transition metal oxide catalyst, specifically to a method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor. Background Technology
[0002] Volatile organic compounds (VOCs) are key components of air pollution, exhibiting significant chemical stability, biotoxicity, and recalcitrant degradation, posing a serious threat to the ecological environment and human health. Therefore, developing economical and efficient VOCs treatment technologies is crucial for environmental protection and human health. Among numerous VOCs treatment technologies, thermocatalytic oxidation is widely considered an effective technology for removing pollutants from the atmosphere due to its high efficiency and environmental friendliness (the main degradation products are CO2 and H2O). However, the high cost and susceptibility to poisoning of precious metal catalysts greatly limit their commercial application. In contrast, transition metal elements, especially manganese (Mn), are often used as active components in the catalytic oxidation of VOCs due to their abundant resources and excellent catalytic activity, exhibiting good catalytic degradation performance for most VOCs components, such as propane. It is worth noting, however, that different preparation methods and post-synthetic modifications can affect the specific surface area, morphology, and defect density of the catalyst, thereby influencing its catalytic activity. For example, in the preparation of transition metal oxide catalysts, methods such as hydrothermal synthesis and co-precipitation can lead to excessively high local catalyst concentrations, agglomeration, or uneven composition, resulting in low efficiency and high energy consumption, thus reducing catalyst performance. Furthermore, the specific surface area of transition metal oxide catalysts obtained by existing methods needs further optimization.
[0003] Therefore, it is necessary to address the problems caused by the existing methods for preparing transition metal oxide catalysts, such as excessively long reaction times, agglomeration, or insufficient uniformity of composition, while simultaneously increasing the specific surface area of transition metal oxide catalysts. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor. This synthesis method has the advantages of short reaction cycle, low agglomeration, uniform product composition, and large specific surface area of the catalyst.
[0005] The present invention relates to a method for preparing defect-rich transition metal oxide catalysts derived from bio-based complex precursors, using a bio-based complexing agent as an organic ligand and a transition metal as an active component, and employing a mechanochemical method to prepare the transition metal oxide catalyst.
[0006] Furthermore, the bio-based complexing agent has a highly branched bundle structure and is rich in hydroxyl groups. The active component is a salt containing a transition metal. Mechanical ball milling is used to dope the transition metal and construct the surface oxygen vacancies to prepare a layered transition metal oxide catalyst.
[0007] Furthermore, the bio-based complexing agent is corn amylopectin, and the transition metal-containing salt is a manganese salt;
[0008] Furthermore, the following steps are included:
[0009] S1, Preparation of bio-based complex precursor: The bio-based complexing agent, a salt containing a transition metal, and a solvent are mixed and ball-milled, and then the resulting gel product is dried;
[0010] S2, Preparation of transition metal oxides: Calcining the dried gel product;
[0011] Furthermore, in step S1, vacuum drying is used, and the drying temperature is 50-70℃;
[0012] Furthermore, in step S1, the mass ratio of the transition metal-containing salt to the bio-based complexing agent is 1:0.01-0.6;
[0013] Furthermore, in step S1, the balls used in the ball mill are two-stage graded corundum balls;
[0014] Furthermore, the diameters of the corundum spheres are 1.0 cm and 0.5 cm, respectively;
[0015] Furthermore, in step S2, the calcination temperature is 500-650℃, the heating rate is 4℃ / min, and the temperature is held for 1-2 hours after reaching the set temperature.
[0016] The beneficial effects of this invention are as follows: The method for preparing a bio-based complex precursor-derived defect-rich transition metal oxide catalyst uses a bio-based complexing agent as an organic ligand. Utilizing the abundant hydroxyl groups in the bio-based complexing agent, hydrogen bonds can be formed between other molecules, enhancing intermolecular forces and improving the catalyst's stability and functionality. Through mechanochemical methods for incorporating transition metals and constructing surface oxygen vacancies, the prepared catalyst achieves a conversion rate of over 90% at 370℃ and exhibits excellent catalytic performance for hydrocarbons such as propane. The preparation method of this invention is simple to operate, environmentally friendly, and has good reproducibility. It avoids the problems of excessively long reaction times, agglomeration, or uneven composition caused by other preparation methods, increasing the exposure opportunity of active sites. Simultaneously, it can also increase the specific surface area of the transition metal oxide catalyst, with a maximum specific surface area reaching 81.8 m². 2 / g. Attached Figure Description
[0017] The present invention will be further described below with reference to the accompanying drawings and embodiments:
[0018] Figure 1 The X-ray diffraction (XRD) spectra of the obtained transition metal oxide samples are shown, where the curves MnOx-50mgYMDF, MnOx-100mgYMDF, MnOx-200mgYMDF, MnOx-400mgYMDF, and MnOx-600mgYMDF correspond to the XRD spectra of the samples in Examples 1, 2, 3, 4, and 5, respectively.
[0019] Figure 2 The activity curves of the prepared transition metal oxide samples for the catalytic oxidation of C3H8 are shown, where MnOx-50mgYMDF, MnOx-100mgYMDF, MnOx-200mgYMDF, MnOx-400mgYMDF, and MnOx-600mgYMDF correspond to the activity curves of the samples in Examples 1, 2, 3, 4, and 5, respectively.
[0020] Figure 3 To obtain SEM images of transition metal oxide samples, MnOx-50mgYMDF, MnOx-100mgYMDF, MnOx-200mgYMDF, MnOx-400mgYMDF, and MnOx-600mgYMDF correspond to the SEM images of samples from Examples 1, 2, 3, 4, and 5, respectively. Detailed Implementation
[0021] This embodiment describes a method for preparing defect-rich transition metal oxide catalysts derived from bio-based complex precursors. Using a bio-based complexing agent as the organic ligand and a transition metal as the active component, the catalyst is prepared via a mechanochemical method. Mechanochemistry, in essence, is a process where mechanical energy generated by compression, shearing, impact, and stretching promotes physicochemical transformation. Through collisions, compression, shearing, and friction between the grinding media and the material, chemical reactions are induced, altering the material's internal structure, crystal phase, and surface properties, thereby promoting material modification or chemical reactions. Mechanochemistry offers advantages such as short modification time, high reactivity, and no corrosion, and is considered a green, sustainable, and easily scalable synthetic technology. Compared to other synthetic technologies, mechanochemistry not only offers the possibility of eliminating the use of large amounts of solvents but also provides the opportunity to achieve synthetic strategies, reactions, and molecules previously unattainable in solution. Furthermore, mechanochemistry can generate unique physicochemical properties during synthesis, directly modifying or constraining materials. The transition metal is the active component, typically a salt containing a transition metal. The mechanochemical method of this invention is used for the addition of transition metals and the construction of surface oxygen vacancies.
[0022] In this embodiment, the bio-based complexing agent is a highly branched bundle structure and rich in hydroxyl groups, preferably corn amylopectin, but other bio-based complexing agents with similar physicochemical properties can also be used. The active component is a transition metal salt, preferably manganese nitrate, such as Mn(NO3)2·4H2O. Mechanical ball milling is used to incorporate Mn and construct surface oxygen vacancies to prepare a layered transition metal oxide catalyst. Amylopectin has a highly branched bundle structure and is rich in hydroxyl groups. During the ball milling process with manganese salt, due to hydrolysis and mechanical force, free small molecules are generated, the polymer chains shorten, resulting in a large number of defects and edge dislocation structures, and exposing more catalytic active sites. This also provides feasibility for preparing defect-rich transition metal oxides derived from bio-based complex precursors.
[0023] This embodiment includes the following steps:
[0024] S1, Preparation of bio-based complex precursor: A bio-based complexing agent, a transition metal-containing salt, and a solvent are mixed and ball-milled to obtain a gel product. The resulting gel product is then vacuum-dried at a temperature of 50-70℃; the vacuum drying temperature can be 50℃, 53℃, 55℃, 57℃, 60℃, 63℃, 65℃, 67℃, 70℃, etc. Anhydrous ethanol solution is generally used as the solvent. The mass ratio of the transition metal-containing salt to the bio-based complexing agent is 1:0.01-0.6. The ball milling balls are two-stage graded corundum balls with diameters of 1.0 cm and 0.5 cm, respectively. Using two-stage graded balls makes the reaction less sensitive to changes in the material, resulting in a relatively stable yield. The gaps between the large balls are filled by smaller balls to fully improve the packing density of the steel balls. Large balls can impact and crush materials, improving the mill's impact capability and number of impacts, which meets the functional characteristics of grinding media; while small balls can fill the gaps between large balls, increasing the bulk density of the grinding media to control the material flow rate; in addition, they can also expel coarse particles from the gaps and place them in the impact zone of the large balls.
[0025] S2, Preparation of transition metal oxides: Calcine the dried gel product, heat it to the set temperature at a heating rate of 4℃ / min, and hold it for 1-2 hours. The set temperature is 500-650℃, such as 500℃, 520℃, 540℃, 560℃, 580℃, 600℃, 620℃, 650℃, etc.
[0026] Example 1
[0027] Mn(NO3)2·4H2O (2.51 g, 10 mmol) and corn amylopectin (50 mg) were placed in a zirconia ball milling jar (50 mL) containing fifteen corundum balls (three with a diameter of 1.0 cm and fifteen with a diameter of 0.5 cm) and milled for 20 min. The resulting gel product was washed three times by centrifugation with anhydrous ethanol and dried in a vacuum oven at 60 °C for 2 h. Finally, the temperature was increased to 550 °C at 4 °C / min and held for 2 h to obtain the transition metal oxide catalyst.
[0028] Example 2
[0029] Mn(NO3)2·4H2O (2.51 g, 10 mmol) and corn amylopectin (100 mg) were placed in a zirconia ball milling jar (50 mL) containing fifteen corundum balls (three with a diameter of 1.0 cm and fifteen with a diameter of 0.5 cm) and milled for 20 min. The resulting gel product was washed three times with anhydrous ethanol by centrifugation and dried in a vacuum oven at 60 °C for 2 h. Finally, the temperature was increased to 550 °C at 4 °C / min and held for 2 h to obtain the transition metal oxide catalyst.
[0030] Example 3
[0031] Mn(NO3)2·4H2O (2.51 g, 10 mmol) and corn amylopectin (200 mg) were placed in a zirconia ball milling jar (50 mL) containing fifteen corundum balls (three with a diameter of 1.0 cm and fifteen with a diameter of 0.5 cm) and milled for 20 min. The resulting gel product was washed three times with anhydrous ethanol by centrifugation and dried in a vacuum oven at 60 °C for 2 h. Finally, the temperature was increased to 550 °C at 4 °C / min and held for 2 h to obtain the transition metal oxide catalyst.
[0032] Example 4
[0033] Mn(NO3)2·4H2O (2.51 g, 10 mmol) and corn amylopectin (400 mg) were placed in a zirconia ball milling jar (50 mL) containing fifteen corundum balls (three with a diameter of 1.0 cm and fifteen with a diameter of 0.5 cm) and milled for 20 min. The resulting gel product was washed three times by centrifugation with anhydrous ethanol and dried in a vacuum oven at 60 °C for 2 h. Finally, the temperature was increased to 550 °C at 4 °C / min and held for 2 h to obtain the transition metal oxide catalyst.
[0034] Example 5
[0035] Mn(NO3)2·4H2O (2.51 g, 10 mmol) and corn amylopectin (600 mg) were placed in a zirconia ball milling jar (50 mL) containing fifteen corundum balls (three with a diameter of 1.0 cm and fifteen with a diameter of 0.5 cm) and milled for 20 min. The resulting gel product was washed three times by centrifugation with anhydrous ethanol and dried in a vacuum oven at 60 °C for 2 h. Finally, the temperature was increased to 550 °C at 4 °C / min and held for 2 h to obtain the transition metal oxide catalyst.
[0036] Test Example 1:
[0037] XRD tests were performed on the MnOx-50mg YMDF, MnOx-100mg YMDF, MnOx-200mg YMDF, MnOx-400mg YMDF, and MnOx-600mg samples from Examples 1-4, respectively. The test results are as follows: Figure 1 As shown, the MnOx-50mgYMDF, MnOx-100mgYMDF, MnOx-200mgYMDF, MnOx-400mgYMDF, and MnOx-600mg samples all contain Mn2O3 and Mn3O4. With the increase of KMnO4 content, the amorphousness of the prepared catalyst increases, and the larger offset angle may be the result of increased crystal plane defects or lattice distortion.
[0038] Test Example 2:
[0039] The catalytic oxidation activity of MnOx-50mgYMDF, MnOx-100mgYMDF, MnOx-200mgYMDF, MnOx-400mgYMDF, and MnOx-600mgYMDF samples from each embodiment was evaluated in a fixed-bed reactor system. 50mg of sample was mixed thoroughly with 0.85g of quartz sand and placed in a quartz tube reactor. The total flow rate of the reaction mixture (89 vol% N2 + 10 vol% O2 + 1 vol% C3H8) was 100 mL / min, corresponding to a mass hourly space velocity (MSV) of 120,000 mL·g. -1· h -1 The reaction temperature is controlled by thermocouples located inside the catalyst bed. The concentration of C3H8 in the mixed gas after passing through the catalyst is monitored online by a gas detection device.
[0040] Test Example 3:
[0041] Scanning electron microscopy (SEM) was performed on the MnOx-50mg YMDF, MnOx-100mg YMDF, MnOx-200mg YMDF, MnOx-400mg YMDF, and MnOx-600mg samples from Example 3. The results are as follows: Figure 3The images show SEM images of the samples. As can be seen from the figures, the morphology of the catalyst changes significantly with the increase of corn amylopectin content. When the corn amylopectin content is 50 mg and 100 mg, the catalyst appears flocculent with surface particle accumulation. When the corn amylopectin content is 200 mg, the catalyst appears as a uniform porous sheet. When the corn amylopectin content is 400 mg and 600 mg, the catalyst gradually agglomerates, forming powder or lumps that are small sheet-like accumulations, and the number of pores on the catalyst surface decreases.
[0042] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor, characterized in that: Transition metal oxide catalysts were prepared by a mechanochemical method using bio-based complexing agents as organic ligands and transition metals as active components.
2. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 1, characterized in that: The bio-based complexing agent has a highly branched bundle structure and is rich in hydroxyl groups. The active component is a salt containing a transition metal. Mechanical ball milling is used to dope the transition metal and construct the surface oxygen vacancies to prepare a layered transition metal oxide catalyst.
3. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 2, characterized in that: The bio-based complexing agent is corn amylopectin, and the transition metal-containing salt is a manganese salt.
4. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 2, characterized in that: Includes the following steps: S1, Preparation of bio-based complex precursor: The bio-based complexing agent, a salt containing a transition metal, and a solvent are mixed and ball-milled, and then the resulting gel product is dried; S2, Preparation of transition metal oxides: Calcine the dried gel product.
5. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 4, characterized in that: In step S1, vacuum drying is used, and the drying temperature is 50-70℃.
6. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 4, characterized in that: In step S1, the mass ratio of the transition metal salt to the bio-based complexing agent is 1:0.01-0.
6.
7. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 4, characterized in that: In step S1, the balls used in the ball mill are two-stage graded corundum balls.
8. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 7, characterized in that: The diameters of the corundum spheres are 1.0 cm and 0.5 cm, respectively.
9. The method for preparing a defect-rich transition metal oxide catalyst derived from a bio-based complex precursor according to claim 4, characterized in that: In step S2, the calcination temperature is 500-650℃, the heating rate is 4℃ / min, and the temperature is held for 1-2 hours after reaching the set temperature.